IMPACT OF LEGISLATIVE CHANGES ON THE FINANCING OF JUDICIAL ACTIVITIES IN UKRAINE - Ірина Личенко; Ірина Андрусяк; Зоряна Гонтар; Юрій Норчук; Вікторія Питльована; Сніжана Панченко (Фінансово-кредитна діяльність: проблеми теорії та практики, 2024)
Judicial activity in Ukraine involves the examination and resolution of contentious issues related to the protection of rights, restoration of violated rights, cessation of rights violations, and application of legal influence measures. All these require appropriate resources, not just informational but also financial and material. The levels of funding depend on the judicial authority financing programs and state budget projects. In other words, changes in legislation will directly affect the volumes and timelines of funding for judicial activities. Conducting an in-depth analysis of scientific and practical literature, our goal was to identify and assess the level of impact of the latest legislative changes on the funding volumes for judicial activities in Ukraine. The object of the study is judicial activity in Ukraine. We believe that the assessment of legislative changes requires the involvement of relevant experts in law and beyond. Therefore, with the help of experts and the applied structuring technique, the weight of the impact of certain legislative changes on the amount of funding for judicial activity in Ukraine is ranked. However, determining which impact is most significant is just one of the outcomes. Additionally, measures for the judicial system's response/adaptation to the most significant changes were proposed. The limitations of the study relate to the fact that the legislative changes identified in the work are not constant and stable. In the future, there will be new changes requiring a new approach to evaluation and response.